Ripples and Fast Ripples as Markers for Epileptogenic Zone in TS Complex - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators from the Hospital for Sick Children, Toronto, Canada, and Okayama University Hospital, Japan, analyzed the high occurrence rate (OR) of interictal high frequency oscillations (HFOs) at 80-200 Hz (ripples) and >200 Hz (fast ripples, FRs).